Character Determination in Elementary School Children of Madrasah Ibtidaiyah Al Jamiyatul Washliyah in 2021 Based on the Fingerprint of Right Hands - Hasibuan, Dewi Astuti; Petrus, Asan (Jour Med Resh and Health Sci, 2021)
Objective:To find out the character of elementary school students through fingerprint analysis. Method:This research is descriptive research. The research subjects were 43 students of Ibtidaiyah Al Jamiyatul Washliyah Elementary School in September 2021 until the number of samples was met. Student fingerprints are taken by placing the tips of the fingers on the stamp pads that have been given ink, then affixed to white paper to form fingerprints. This is done to completion on each student's right thumb. From the obtained fingerprints, direct observations were made on the fingerprint pattern (loop pattern, arch pattern, and whorl pattern). Collecting non-fingerprint data in the form of name and gender. Results:Get an effective learning system by getting to know the character of each student. Conclusion: Fingerprints can be used to identify students' characters. By getting to know the character of students, teachers can get to know better about students and create a better learning system. The frequency of Loop pattern fingerprints is more in women as much as 15 (32.6%) than men as many as 6 (13.04%) with a total The total Loop fingerprint pattern is 21 (45.6%) and this is in accordance with the results of Galton's research which states that the Loop fingerprint pattern frequency is higher than the Whorl and Arch forms.